PEMANFAATAN BAHAN AJAR PAI BERBASIS CERITA ISLAMI UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS V SDN 186 LEMBANG KABUPATEN PINRANG - Asikin, Nur; Usman; Munirah (Primer Edukasi Journal, 2025)
This research aims: 1) To determine the learning motivation of students who are taught without using Islamic story-based PAI teaching materials for class V at SDN 186 Lembang, Pinrang Regency. 2) Knowing the learning motivation of students who are taught using PAI teaching materials based on Islamic stories for class V SDN 186 Lembang, Pinrang Regency. 3) Knowing the difference in learning motivation of students who are taught without using Islamic story-based PAI teaching materials and the learning motivation of students who are taught using Islamic story-based PAI teaching materials for class V SDN 186 Lembang, Pinrang Regency. This research uses a quasi-experimental experimental design in the form of a nonequivalent control group design. The research results show that the largest percentage of control class students' learning motivation is in the medium category, namely 7 respondents' answers and the largest percentage of experimental class students' learning motivation is in the medium category, namely 6 respondents' answers. Based on the results of the hypothesis test that has been carried out, it can be seen that the variance of the two data is homogeneous, so the Equal variances assumed column is selected, and the t-test for Equality of Means row shows that the value is t = 19,247, df = 18, and Sig.(2-tailed) is equal to 0.000 < 0.05 or H₀ is rejected. So there is a difference in the learning motivation of students who are taught without using Islamic story-based PAI teaching materials and the learning motivation of students who are taught using Islamic story-based PAI teaching materials for class V SDN 186 Lembang, Pinrang Regency. Keywords: PAI Teaching Materials, Islamic Stories, Learning Motivation.